2016
DOI: 10.1093/mnras/stw041
|View full text |Cite
|
Sign up to set email alerts
|

Absorption at 11 μm in the interstellar medium and embedded sources: evidence for crystalline silicates

Abstract: An absorption feature is occasionally reported around 11 µm in astronomical spectra, including those of forming stars. Candidate carriers include water ice, polycyclic aromatic hydrocarbons (PAHs), silicon carbide, crystalline silicates or even carbonates. All are known constituents of cosmic dust in one or more types of environments, though not necessarily together. In this paper we present new ground-based 8-13 µm spectra of one evolved star, several embedded young stellar objects (YSOs) and a background sou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 191 publications
1
15
0
Order By: Relevance
“…The cycling of dust between dense and diffuse interstellar media during cycles of cloud collapse (a-C:H mantle accretion) and star formation (a-C:H mantle photo-processing to a-C) would probably lead to the accumulation of thicker a-C(:H) mantles, which would nevertheless be progressively eroded during their sojourn in the low-density ISM. Thus, in the same way that silicate dust in the ISM has been processed to an amorphous form [32,33], with some small fraction remaining unprocessed and crystalline [122], carbonaceous dust would be expected to show these same traces, despite perhaps being more fragile [31,66,69]. Thus, carbonaceous core/mantle grains ought to present a range of compositions depending on their exposure to irradiation (by photons, electrons and ions) in the ISM, i.e.…”
Section: Dust: Evolved Grain Mantlesmentioning
confidence: 99%
“…The cycling of dust between dense and diffuse interstellar media during cycles of cloud collapse (a-C:H mantle accretion) and star formation (a-C:H mantle photo-processing to a-C) would probably lead to the accumulation of thicker a-C(:H) mantles, which would nevertheless be progressively eroded during their sojourn in the low-density ISM. Thus, in the same way that silicate dust in the ISM has been processed to an amorphous form [32,33], with some small fraction remaining unprocessed and crystalline [122], carbonaceous dust would be expected to show these same traces, despite perhaps being more fragile [31,66,69]. Thus, carbonaceous core/mantle grains ought to present a range of compositions depending on their exposure to irradiation (by photons, electrons and ions) in the ISM, i.e.…”
Section: Dust: Evolved Grain Mantlesmentioning
confidence: 99%
“…Unfortunately, the conventional spectrum of MWC 1080A given by Sakon et al (2007) does not show any such apparent absorption feature around 11.2 µm which contradicts the findings of our model. While most cases of crystalline silicate detection have been reported in emission [Watson et al (2009);Olofsson et al (2009);Juhász et al (2010)], recent studies have shown a considerable number of such features in absorption as well [Poteet et al (2011);Fujiyoshi et al (2015); Wright et al (2016)]. All three objects in our sample of study: MWC 1080A, MWC 297 and HL Tau, show polarization in absorption but only the MWC 1080A polarization seems to have been caused due to SiC mixed with silicates.…”
Section: Discussionmentioning
confidence: 53%
“…Polarization is represented as the difference between the parallel and perpendicular components of extinction efficiency which are independently related to the dust optical constants [Whittet (2003)]. The polarization profile (peak wavelength, shape and strength) is highly susceptible to the specific shape, composition as well as dust grain size and hence, the study of polarization across an absorption/emission feature can be very efficiently used to constrain these properties [Dullemond & Dominik (2008); Fujiyoshi et al (2015); Wright et al (2016)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the DL model may be incompatible with the latest findings of grain materials and sizes in the local interstellar medium, most of which have been presented in a series of Cosmic Dust meetings: The size distribution of interstellar grains is skewed toward heavier masses by more than one order of magnitude and has a shallower powerlaw index than expected from the DL model (Kimura et al, 2003;Sterken et al, 2015); There is no evidence for the presence of carbonaceous materials in interstellar grains measured by Cassini and Stardust, although graphite grains, if exist as in the DL model, should have been identified by Cassini (Kimura et al, 2015b;Westphal, 2015); Interstellar grains extracted from the aerogel collector of Stardust contain forsteritic olivine, contrary to amorphous silicate expected from the DL model (Westphal, 2015;Westphal et al, 2014). Very recently, Wright et al (2016) have found evidence for crystalline silicates in the interstellar medium from their infrared spectral observations toward the Galactic Center, in contrast to the DL model. Furthermore, it turned out that interstellar grains are compositionally homogeneous and seem to contain magnesium-rich silicates and metallic iron, dissimilar from Mg 1.1 Fe 0.9 SiO 4 in the DL model (Altobelli et al, 2016).…”
Section: Perspectives For the Development Of Cosmic Dust Researchmentioning
confidence: 99%